Selection of Raw Material Suppliers for Leather Handicrafts Using The Analytical Hierarchy Process - Sitti Nabila; Reni Dwi Astuti Reni (Jurnal Ilmiah Dinamika Rekayasa, 2026)
Suppliers are an essential factor to consider in supply chain management. So far, the MSME House of Makario, which produces leather handicrafts, has yet to have a specific mechanism for selecting raw material suppliers. As a result, the arrival time, price, and quality of raw materials must match the order. This research aims to determine the leading suppliers with quality, price, delivery, and service criteria. The method used is the Analytical Hierarchy Process (AHP)—data collection using questionnaires, interviews, and literature studies. The data processing results show the priority criteria: quality with a weight of 40%, price of 32%, delivery at 20%, and service at 8%. The priority weight order of the selected suppliers is Supplier A by 35%, Supplier B by 34%, and Supplier C by 31%. Thus, Supplier A is a supplier that is recommended to be the leading supplier.